THE EFFECT OF STATEGIC MANAGEMENT ON MANAGERIAL PERFORMANCE WITH STRATEGIC IMPLEMENTATION AS A MODERATING VARIABLES (EMPIRICAL STUDY OF THE PULO GADUNG INDUSTRIAL AREA, JAKARTA) - Apollo, Apollo (Dinasti International Journal of Economics, Finance & Accounting, 2020)
This study aims to obtain empirical evidence of the influence of external factors, internal factors, strategic planning, strategic implementation on managerial performance. The research unit is 66 respondents on Banking in Jakarta. Methods of analysis tools using path analysis or a combination of correlation and regression to determine the effect of partially or simultaneously. This study was conducted with two models: 1st Model: Influence of External Factors (X1), Internal Factors (X2), Strategic Planning (X3), and the Strategic Implementation (M) on Managerial Performance (Y) either partially or simultaneously among others: partially: the influence of external factors (X1) on managerial performance (Y) of 75.8 % significantly by 0,011, or 11 %, the effect of internal factors (X2) on managerial performance (Y) equal to 61.8 % of non significant ; influence planning strategic (X3) on managerial performance (Y) equal to 74.2 % of non significant ; influence the strategic implementation (M) on managerial performance (Y) by 5 % non- significant . Simultaneously: the influence of external factors (X1), internal factors (X2), strategic planning (X3), and strategic implementation (M) on managerial performance (Y) by a significant 60.2 %. 2nd Model: Influence of External Factors (X1), Internal Factors (X2), and Strategic Planning (X3), the Managerial Performance (Y) with Strategic Implementation (M) as a moderating variable either partially or simultaneously among others: The results of this study have consistency with the entire framework, literature review, and previous studies . The suggestion for the study: (a) for the development of advanced management accounting research is needed outside the model, such other factors which managerial performance (b) to formulate clear policies and management needs to be more concrete criteria above considerations external factors, internal factors, strategic planning, and implementing strategies to improve the performance of managerial